Biosurfactant Production by A Bacterial Strain Pseudomonas Aeruginosa MTCC 16036 - Kanna, Rajesh (International Journal of Engineering and Technology, 2018)
Microbial compounds which has the potential to exhibit emulsification and surface activities are classified as termed as biosurfactants. Compared to that of a chemically synthesized surfactant, these biosurfactants are considered to be environmental friendly, exhibits lower toxicity and active even at extreme temperatures, pH and saline conditions. The current research is focused on biosurfactant production using Pseudomonas aeruginosa MTCC 16036 further it is evaluated for oil recovery from trapped petroleum reservoir. Studies on selection of best carbon and nitrogen sources were tested for enhanced biosurfactant production using nutrient medium. Among the tested sources, glucose and urea were found to be the best carbon and nitrogen source. The effect of initial pH was studied by varying pH from 5.0 â€“ 8.0 and maximum biosurfactant production 2.8 g/L was achieved at pH of 8.0. Produced biosurfactant reduced interfacial tension (8mN/m) which is the key parameter for recovering residual oil.Â Further, the stability of produced biosurfactant wasinvestigated by varying pH (1.0 â€“ 12.0) and temperature (40 â€“ 120 Â°C).Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â